An investigation into the effects of different warm-up modalities on specific motor skills related to soccer performance - Fletcher, I. M.; Monte-Colombo, M. M. (The Journal of Strength and Conditioning Research, 2010)
The aim of this study was to investigate the effect of different warm-up stretch modalities on specific high-speed motor capabilities important to soccer performance. Twenty-seven male soccer players performed 3 warm-up conditions, active warm-up (WU), WU with static stretching (SPS), and WU with dynamic stretching (ADS). Heart rate, countermovement jump, 20-m sprint, and Balsom agility tests were performed after each intervention. Vertical jump heights were significantly greater (p < 0.01) in the WU and ADS conditions compared to those in the SPS trial. The 20-m sprint and agility times showed that the SPS condition was significantly slower (p < 0.01) than the WU and ADS conditions, with the ADS trial being significantly faster (p < 0.05) than the WU condition. Heart rate was significantly higher (p < 0.01) for participants post-WU and -ADS trials compared to the SPS condition. These findings suggest that the superior performance of the dynamic stretch and warm-up-only conditions compared to the static stretch condition may be linked to increases in heart rate. The reasons for the dynamic stretch trial superiority compared to the warm-up condition are less clear and as yet to be established. We recommend for optimal performance, specific dynamic stretches be employed as part of a warm-up, rather than the traditional static stretches.